The Use of Vibrational Energy to Isolate Adipose-Derived Stem Cells. Issue 1 (January 2018) - Packer, Jonathan D.; Chang, Wen-Teh; Dragoo, Jason L.
Abstract : Background: Adipose-derived stem cell (ADSC)–based treatments have the potential to treat numerous soft-tissue pathologies. It would be beneficial to develop an efficient and reliable intraoperative, nonenzymatic method of isolating ADSCs for clinical use. This study aims to determine the (1) viability and proliferative capacity of ADSCs after exposure to vibrational energies and (2) efficacy of vibrational energy as a method of ADSC isolation from surgically harvested infrapatellar fat pad (IFP). Methods: Cultured ADSCs were exposed to 15 minutes of vibration (60 Hz) with displacements ranging from 0 to 2.5 mm to assess cell viability and proliferation. Then, arthroscopically harvested adipose tissue (IFP; n = 5 patients) was filtered and centrifuged to separate the stromal vascular fraction, which was exposed to 15 minutes of vibration (60 Hz; 1.3 mm or 2.5 mm displacement). A viability analysis was then performed along with proliferation and apoptosis assays. Results: Vibration treatment at all displacements had no effect on the viability or proliferation of the cultured ADSCs compared with controls. There was an increased apoptosis rate between the 2.5 mm displacement group (7.53%) and controls (5.17%; P < 0.05) at day 1, but no difference at days 2, 3, and 14. ADSCs were not isolated from the IFP tissue after vibration treatment. Conclusions: ADSCs maintained viability and proliferative capacity after 15 minutes of vibration at 60 Hz and 2.5 mm displacement. ADSCs were not isolated harvested IFP tissue after the application of vibrational energy.